ACTION OF SYNTHETIC DETERGENTS ON THE METABOLISM OF BACTERIA - Baker, Zelma (The Rockefeller University Press, 1941)
A study of the effects of synthetic detergents and wetting agents on respiration and glycolysis of Gram-positive and Gram-negative microorganisms has led to the following conclusions. 1. All the cationic detergents studied are very effective inhibitors of bacterial metabolism at 1:3000 concentration, and several are equally active at 1:30,000. Few of the anionic detergents inhibit as effectively as the cationic compounds. 2. Gram-positive and Gram-negative microorganisms are equally sensitive to the action of the cationic detergents. On the other hand, all the anionic detergents included in our studies selectively inhibit the metabolism of Gram-positive microorganisms. 3. The inhibitory action of both types of detergents is influenced markedly by hydrogen ion concentration. Cationic detergents exhibit their maximum activity in the alkaline pH range, and the anionic, in the acid range. 4. Studies of homologous series of straight chain alkyl sulfates and sulfoacetates (C(8) to C(18)) demonstrate that maximum inhibition is exerted by the 12, 14, and 16 carbon compounds (lauryl, myristyl, and cetyl). 5. It has been observed that three lauryl esters of amino acids are powerful inhibitors of bacterial metabolism. To our knowledge, the effects on bacterial metabolism of such cationic detergents (without the quaternary ammonium structure) have not been studied previously. Our results demonstrate that other cationic detergents can exhibit an inhibitory activity comparable to quaternary ammonium compounds. 6. Certain detergents stimulate bacterial metabolism at concentrations lower than the inhibiting values. This effect has been found more frequently among the anionic detergents.